Treatment of Paracetamol in Water with Different Salinities over Powder and Supported TiO2 and ZnO Photocatalysts - Saepurahman, Saepurahman; Mulyani, Gina; Sambudi, Nonni Soraya; Kurniawan, Teguh (Universitas Jenderal Soedirman, 2024)
ABSTRACT. Paracetamol's (PCT) Paracetamol's (PCT) presence in water bodies poses a risk to both aquatic life and humans. This study aims to examine the effect of salinities on PCT removal in water using powder and supported photocatalysts. ZnO powder is a superior photocatalyst to TiO2, where the rate constant can be 18 times higher. Salinity boosted the PCT removal up to 2.7 times for TiO2 at lower concentrations but decreased the PCT removal for TiO2 and ZnO at higher values. Immobilizing the powder photocatalysts on a nonwoven polyester support (NPS) dropped the photocatalytic activity, especially for ZnO, whose performance was 36 times lower than its powder counterpart. The passivation of the photocatalysts by the silica binder necessary for attaching the photocatalyst to the support can be linked to the decline in the performance of TiO2 and ZnO composites. The silica and TiO2 formed homogeneous layers on the NPS, unlike the silica and ZnO layers. High salinity reduced the performance of TiO2 composites by 20 times but showed no significant effect on ZnO composites. The performance of the ZnO composite was further reduced when real seawater was used as feed. Keywords: Titanium dioxide, zinc oxide, polyester, paracetamol, salinity.